Analyzing Factors Affecting Employee Productivity: Training, Discipline, and Experience: Dampak Pelatihan, Disiplin, dan Pengalaman Kerja terhadap Produktivitas Karyawan: Analisis Kuantitatif - Dziki Nur Alif Fatul Anwar; Vera Firdaus (Academia Open, 2023)
This study examines the relationship between training, discipline, work experience, and employee work productivity using an associative quantitative approach. A questionnaire was administered to 50 purposively sampled employees from PT. Prima Karya Teknik. The data were analyzed using SPSS version 22, employing validity and reliability tests, classical assumption tests, multiple linear regression, f-tests, t-tests, correlation tests, and determination tests. The results indicate that training, discipline, and work experience all positively and significantly influence employee work productivity. The findings suggest that investing in training programs, promoting discipline, and recognizing the value of work experience can enhance employee productivity. These findings hold implications for organizations seeking to optimize their workforce performance and foster a productive work environment. Highlights: Effective training programs positively impact employee work productivity. Maintaining discipline in the workplace enhances employee work productivity. Work experience plays a significant role in improving employee work productivity. Keywords: training, discipline, work experience, employee productivity, quantitative analysis.